2018
DOI: 10.1002/app.46634
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life prediction via the time‐dependent evolution of linear and nonlinear mechanical parameters determined via Fourier transform of the stress

Abstract: This study proposes a new concept for the lifetime prediction of solid polymers under mechanical fatigue. The time evolution of linear and nonlinear mechanical parameters was studied using polystyrene (PS), polymethylmethacrylate (PMMA), and styrene‐acrylonitrile (SAN) samples in strain controlled (large amplitude) oscillatory shear (torsion). Higher harmonics of the stress were detected and quantified via Fourier transform (FT). Besides storage and loss modulus (G′, G″), the ratio of the third (I3) harmonic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…With ongoing fatigue, the nonlinear mechanical parameter I 3/1 was found to monotonously increase (for rectangular and notched specimens). [ 4, 16, 17 ] On the other hand, the even higher harmonics can be associated with asymmetries caused by the loading conditions, such as T/T, or an anisotropy in the specimen, such as cracks, plastic deformation, or buckling. Therefore, the first even higher harmonic ( I 2/1 ) was found to be a very sensitive parameter towards crack detection.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…With ongoing fatigue, the nonlinear mechanical parameter I 3/1 was found to monotonously increase (for rectangular and notched specimens). [ 4, 16, 17 ] On the other hand, the even higher harmonics can be associated with asymmetries caused by the loading conditions, such as T/T, or an anisotropy in the specimen, such as cracks, plastic deformation, or buckling. Therefore, the first even higher harmonic ( I 2/1 ) was found to be a very sensitive parameter towards crack detection.…”
Section: Theorymentioning
confidence: 99%
“…Recently, a framework was developed to analyze, quantify, and predict the fatigue behavior via the discrete Fourier transform of the stress response by individually analyzing each higher harmonic for brittle polymers under torsion and tension. Three concepts based on the higher harmonics were introduced: (1) the detection of macroscopic cracks via the I 2/1 intensity, [ 16 ] (2) the prediction of fatigue failure via the rate of change of the I 3/1 intensity, [ 17 ] and (3) the cumulative nonlinearity Q f as a fatigue criterion. [ 23 ]…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…A new control method to improve the quality and production efficiency of carbon fiber tow was found. [13][14][15] After studying many predictive control models, we found that some production systems have certain internal and external disturbances. [16][17][18] Complicated uncertainties are difficult to calculate accurately so we are limited and cannot analyze all of the influencing factors.…”
Section: Introductionmentioning
confidence: 99%